Penataan Pemilihan Kepala Desa dalam Sistem Ketatanegaraan di Indonesia - Mohamad Mova Al'afghani; Bisariyadi Bisariyadi (Constitutional Court of the Republic of Indonesia, Indonesia, 2022)
The current political and legal configuration of the village head election organizing institution is not yet in accordance with election governance with integrity. This happens because the institutional structure is not well ordered. This research examines the problem of legal regulation of the structure of the village head election institution, and looks for the ideal framework for the organization to organize the village head election in the future. The research method used is normative and doctrinal legal research method which is carried out by analyzing positive legal norms. Data collection techniques are carried out by reviewing applicable laws and regulations, books and other literature. The results showed that the legal arrangements for village head election organizers through related regulations led to many institutional structures for village head elections so that the funding for village head elections would be expensive. The idea of an ideal framework for an organizing institution for village head elections in the future can be done by shifting the model of the village head election organizing institution from a government model to an independent model. The application of this model can be done through a legislative or executive review of regulations related to village head elections, and at least including the KPU as the organizing agency for village head elections.